Space Flight-Promoted Insulin Resistance as a Possible Disruptor of Wound Healing - Strollo, F.; Gentile, S.; Pipicelli, A. M. V.; Mambro, A.; Monici, M.; Magni, P. (Frontiers in Bioengineering and Biotechnology, 2022)
During space flight, especially when prolonged, exposure to microgravity results in a number of pathophysiological changes such as bone loss, muscle atrophy, cardiovascular and metabolic changes and impaired wound healing, among others. Interestingly, chronic low-grade inflammation and insulin resistance appear to be pivotal events linking many of them. Interestingly, real and experimental microgravity is also associated to altered wound repair, a process that is becoming increasingly important in view of prolonged space flights. The association of insulin resistance and wound healing impairment may be hypothesized from some dysmetabolic conditions, like the metabolic syndrome, type 2 diabetes mellitus and abdominal/visceral obesity, where derangement of glucose and lipid metabolism, greater low-grade inflammation, altered adipokine secretion and adipocyte dysfunction converge to produce systemic effects that also negatively involve wound healing. Indeed, wound healing impairment after traumatic events and surgery in space remains a relevant concern for space agencies. Further studies are required to clarify the molecular connection between insulin resistance and wound healing during space flight, addressing the ability of physical, endocrine/metabolic, and pharmacological countermeasures, as well as nutritional strategies to prevent long-term detrimental effects on tissue repair linked to insulin resistance. Based on these considerations, this paper discusses the pathophysiological links between microgravity-associated insulin resistance and impaired wound healing.